2011
DOI: 10.1111/j.1473-2165.2011.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Side effects and complications of fractional 1550-nm erbium fiber laser treatment among Asians

Abstract: Fractional erbium laser treatment in Asian skin is quite safe, and the side effects in this study were relatively low. Herpes prophylaxis may not be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The study found that PIH was the most common side effect, at 2.2%, which mostly occurred after first treatment and progressively subsided with topical hydroquinone cream. 70 In conclusion, fractional laser resurfacing has lower rate of post-procedure complications than conventional ablative lasers. However, in patients with skin of color, physicians should use lower energy setting, fewer passes or treatment density, and appropriate skin cooling to prevent postinflammatory hyperpigmentation.…”
Section: Fractional Lasersmentioning
confidence: 89%
See 1 more Smart Citation
“…The study found that PIH was the most common side effect, at 2.2%, which mostly occurred after first treatment and progressively subsided with topical hydroquinone cream. 70 In conclusion, fractional laser resurfacing has lower rate of post-procedure complications than conventional ablative lasers. However, in patients with skin of color, physicians should use lower energy setting, fewer passes or treatment density, and appropriate skin cooling to prevent postinflammatory hyperpigmentation.…”
Section: Fractional Lasersmentioning
confidence: 89%
“…The study found that PIH was the most common side effect, at 2.2%, which mostly occurred after first treatment and progressively subsided with topical hydroquinone cream. 70 …”
Section: Laser and Light-based Devicesmentioning
confidence: 99%
“…Adverse events from laser treatment, especially reported PIH, varied among type of laser modalities such as 2.2% after fractional 1550‐nm Ytterbium/Erbium fiber laser, 35% of acne scar patients treated with fractional erbium‐doped yttrium aluminum garnet (Er:YAG) and 92.3% after the treatment of acne scar ablative fractional CO 2 resurfacing …”
Section: Discussionmentioning
confidence: 99%
“…The overall complication rate following non‐ablative fractional resurfacing is much lower than with traditional ablative resurfacing, having been reported in 3.3–7.6% of cases from large retrospective studies . In the study by Graber et al, 961 patients with skin types I‐V were evaluated and 73 treatments (7.6%) with the 1550‐nm erbium‐doped laser (Fraxel, Reliant Technologies) resulted in complications, with the most common being acneiform eruptions (1.87%) and herpes simplex virus (HSV) outbreaks (1.77%) .…”
Section: Discussionmentioning
confidence: 99%
“…The reported HSV infection rate was even lower and occurred in five treatments (0.6%). A further study evaluated 181 treatments with the fractional 1,550 nm Ytterbium/Erbium laser (Finescan; TNC Medditron Co., Ltd., Thailand) in Asian patients with skin phototypes III‐V . Only six treatments (3.3%) developed complications with the most common adverse event being postinflammatory hyperpigmentation (2.2%).…”
Section: Discussionmentioning
confidence: 99%